A Bibliometric Analysis of Global Research on Japanese Encephalitis From 1934 to 2020 - Xu, Chongxiao; Zhang, Weijia; Pan, Yuefeng; Wang, Guowei; Yin, Qikai; Fu, Shihong; Li, Fan; He, Ying; Xu, Songtao; Wang, Zhenhai; Liang, Guodong; Nie, Kai; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Japanese encephalitis (JE) is a mosquito-borne disease caused by the Japanese encephalitis virus (JEV). The disease is mainly an epidemic in Asia and has been studied for nearly 90 years. To evaluate the research trends of JE, 3,023 English publications between 1934 and 2020 were retrieved and analyzed from the Web of Science database using indicators for publication, country or territory, citation, journal, author and affiliation, keyword co-occurrence cluster and strongest citation bursts detection. The results of the bibliometric analysis and the visualization tools show that the number of annual publications on JE has been increasing. JE has been continuously studied in the USA as well as many Asian countries, such as Japan, China, India, and South Korea; however, only a few publications have high citations. The main research groups of JE in the last 5 years were in China, Japan, and the UK. The keyword co-occurrence analysis and the strongest citation bursts detection revealed that most studies focused on the pathogenic mechanism of JEV, control of outbreaks, immunization with JE vaccine. The research maps on JE obtained by our analysis are expected to help researchers effectively explore the disease.